Playfulness and emotional intelligence of Chinese preschool children: is it parental monitoring so important? - Tun, Ju Ern; Arshat, Zarinah; Ismail, Nellie (TEST Engineering & Management, 2020)
Emotional intelligence develops during the crucial early stage of age among preschool children and many negative impacts may arise and affect their lives due to the deficits in emotional intelligence. Playfulness, has been recognized as an essential element of childhood that are vital for promoting children's emotional development and future mental health. Besides, parents play the major role in building playfulness traits among their children and in benefiting children’s emotional intelligence. This study aims to address potential associations of playfulness and parental monitoring with emotional intelligence and also whether parental monitoring could play its moderator role. Cross sectional questionnaire with Child Behavior Inventory of Playfulness (CBI), Adult Involvement in Media Scale (AIM) and Parents Rating Scales of Emotional Intelligence were available for 217 mothers with children aged 4±6 years in private preschool, Kuala Lumpur. Pearson correlation analyses revealed that children’s playfulness (r = .42, p< .01) and parental monitoring (r = .35, p< .01) were significant positively correlated with emotional intelligence. Hierarchical Multiple Regression analysis disclosed parental monitoring did not moderate the effect of playfulness to emotional intelligence in this study.